Rapid detection of Mycoplasma pneumoniae CARDS toxin in clinical respiratory specimens by a loop-mediated isothermal amplification assay - Fang, Yun; Xie, Panpan; Zhang, Xin; Zhang, Yue; Yang, Ning; Shi, Yinghui; Xin, Ruixia; Bai, Yunbiao; Niu, Wenkai; Yuan, Xin (Frontiers in Cellular and Infection Microbiology, 2025)
In light of the absence of rapid and precise diagnostic laboratory tests for the detection of Mycoplasma pneumoniae (MP), a prominent etiological agent implicated in a range of respiratory infections, we developed and evaluated a rapid and straightforward loop-mediated isothermal amplification (LAMP) assay targeting the MP community-acquired respiratory distress syndrome toxin (CARDS TX) gene. The LAMP assay was performed at 65°C for a duration of 60 min, yielding a minimum detection concentration of MP CARDS TX at 0.4986 pg/μl. The assay exhibited no cross-reactivity with 13 other prevalent pathogens associated with respiratory infections or with other common bacterial toxin genes. To further substantiate the validity of the LAMP assay, 200 pharyngeal swabs or bronchoalveolar lavage (BAL) samples were collected from inpatients diagnosed with community-acquired pneumonia (CAP) between June 2021 and July 2022. The results were compared with those obtained by the quantitative real-time polymerase chain reaction (qPCR) method for verification purposes. Of the 200 clinical specimens, 11 exhibited positive results for MP by LAMP and 10 displayed positive results for MP by qPCR (P = 1.000). In summary, a sensitive, specific, straightforward, and expeditious LAMP method for CARDS TX identification was developed to facilitate rapid detection of MP in point-of-care settings. This assay enables early and accurate diagnosis, even in resource-limited environments, which is important for proper antibiotic treatment and prognosis of MP infection.